Evaluasi Parameter Akustik Objektif Gereja X di Surabaya: Gontjang Prajitno, Regina Ratu, Susilo Indrawati, dan Suyatno - Gontjang Prajitno Gontjang Prajitno; Regina Ratu Regina Ratu; Susilo Indrawati Susilo Indrawati; Suyatno Suyatno (Jurnal Fisika dan Aplikasinya, 2018)
The church is one of the buildings that has a solemn image and wisdom, so the difference from the sound pressure, the loudness of the sound and the sound journey that will determine the quality and quantity of the resulting sound impact the comfort of each congregation and the purpose of each event.In an effort to meet the standards of a church worship space, this research is aimed at knowing the distribution of parameter values residing in the congregation. The parameters evaluated include the spreading of the sound pressure level, the dispersion of the humming time, the distribution of the sound clarity of D50 (definition) and the C80 (clarity) of the musical sound. In this research, the testing was done in the X church worship room in Surabaya. From the measurement and analysis it is found that the value of noise criteria in the X church worship room is NC 40 s.d NC 45. This value is still above the recommended noise level for the function of the church worship room. The humming time parameter ranges from 0.42 to 0.568 seconds.The C80 value ranges from 2.94 dB to 12.38 dB. So overall the value of the humming time has not met the standard and for the value of C80 still not meet the standard. Meanwhile, for the value of D50 which states the clarity of vowel sounds worth between 36.82% to 86.96% has met the standard at some point, for space with speech function.